Instagram as a platrorm for information and public engagement in education developmen in remote area - Ani Rizki Dwi Septi; Nuryanti Nuryanti; Agus Ganjar Runtiko (Universitas Ahmad Dahlan, 2025)
The advancement of digital communication technologies has transformed societal patterns of information exchange, particularly through social media platforms such as Instagram, which enable rapid, visual, and interactive dissemination of messages. In the context of education in remote areas of Indonesia, where access and facilities remain limited, social media offers significant potential as both an information channel and a space for public engagement. This study analyzes how the social community Distrik Berisik employs Instagram as a digital campaign medium to support formal education development through the account @sekolah.tanahair, and examines its role in shaping public opinion and fostering participatory communication. A descriptive qualitative approach was applied, with data collected through observation of Instagram content and document analysis of campaign activities. The analysis was guided by New Media Theory and Digital Campaign Theory to explore strategies of information dissemination, the use of Instagram as a medium for public aspirations, and forms of community participation. Findings reveal that Instagram is strategically utilized by District Berisik as both an educational information platform and a participatory space that highlights the realities of schooling in remote regions. Campaign strategies such as defining objectives, crafting persuasive visual narratives, and engaging audiences were found to influence public awareness of educational inequality and encourage broader community involvement, including attention from stakeholders and government actors. This study contributes to digital communication scholarship by demonstrating the role of social communities in leveraging Instagram as a participatory medium for educational campaigns. Its novelty lies in addressing the underexplored use of Instagram for disseminating information and channeling public aspirations in the context of education development in remote areas of Indonesia.